برهان التلازم بين الاستدلال والمغالطة: دراسة تحليلية مقارنة - مهني، عبدالمنعم فتحي عوض (جامعة الأزهر - كلية اصول الدين والدعوة باسيوط, 2022)
يهدف البحث إلى التحدث عن اللزوم، الذي هو امتناع الانفكاك بين شيئين، ويقصد به الارتباط بين المعنى والموضوع، وبين لوازم المعنى، وأثر ذلك في إيصال المعنى كاملا، وهذا يكون عن طريق دلالة الالتزام أو اللزوم، وأهم ما يميز القرآن الكريم، أنه استعمل اللزوم في التواصل وإيصال المعنى التام والقصد الكامل، وأثر ذلك في استيعاب النص القرآني لمتغيرات الزمان, ويهدف أيضا: إلى محاولة الإشارة إلى بيان ما يحصل منه القطع واليقين بالمعنى الأخص، وهذا ما يظهر أهمية برهان التلازم الاستدلالية، وكيف يعنينا في إثبات العقائد، وكل ذلك عن طريق استخدام الأسلوب المنطقي البرهاني، ومن هنا تبدو القيمة الكبرى لأهمية برهان التلازم وانحصاره في تحصيل اليقين بالمعنى الأخص في المسائل العقدية؛ لأنه الأنسب للاعتقاد، وعلى اعتباره أقوى الأقسام من حيث الدلالة والبرهان, ثم يهدف أيضا إلى مواجهة المغالطات، وتفنيد هذه المواقف والرد عليها من خلال المعايير المنطقية من أجل التوصل إلى أحكام مستقيمة تتفق مع العقول السليمة، فلا يمكن أن يصل الإنسان بتفكيره إلى نتائج مستقيمة دون أن تتجمع لديه الأدلة والبراهين، وعدم توافرها هو السبب في المغالطات الشائعة، وقد أشار القرآن إلى أهمية المعرفة بالموضوع والعلم به قبل إبداء الرأي فيه في كثير من الآيات، وبهذا يعتبر البحث محاولة للكشف عن بعض جوانب الأغاليط التي من شأنها أن تطمس نور العقل، وتحاول أن تزيغ به عن الحق واليقين، والخروج به عن المبادئ الأساسية للتفكير، مثل: الاتساق والترابط والمعقولية، وقد قمت بدراسة هذا الموضوع بالدراسة التحليلية النقدية المقارنة. The research aims to talk about immanence, which is the refusal of separation between two things, and it is intended by the link between the meaning and the subject, and between the prerequisites of the meaning, and the effect of that in communicating the meaning in full, and this is through the indication of commitment or necessity, and the most important thing that distinguishes the Holy Qur'an, is that it used immediacy In communication and conveying the full meaning and the complete intent, and the impact of this on the understanding of the Qur'anic text of the variables of time lt also aims: to try to indicate what categorical and certainty is obtained from in the most specific sense, and this is what shows the importance of proof of inferential correlation, and how it helps us in proving beliefs, all by using the demonstrative logical method, hence the great value of the importance of proof of correlation and its confinement to Gaining certainty in the most specific sense in doctrinal issues; Because it is the most appropriate to believe, and because it is considered the strongest section in terms of evidence and proof, then it also aims to confront fallacies, refute these positions and respond to them through logical criteria in order to reach straight rulings that are consistent with sound minds, It is not possible for a person to reach straight results with his thinking without gathering evidence and proofs, and their lack of availability is the reason for common fallacies, and the Qur'an indicated the importance of knowledge of the subject and knowledge of it before expressing an opinion on it in many verses. Aspects of fallacies that obscure the light of the mind, and try to deviate it from truth and certainty, and deviate from it from the basic principles of thinking, such as: consistency, interdependence, and reasonableness. I have studied this subject in a comparative, analytical, and critical study.
Keywords: القرآن الكريم -- النصوص القرآنية -- التفسير القرآني